2017
DOI: 10.5846/stxb201603010354
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal characteristics of three main land-use types in China based on MODIS data

Abstract: 基金项目:国家林业公益性行业科研专项(201404316) ;湖南省自然科学创新研究群体基金(湘基金委字[2013]7 号) ;国家林业局软科学研究项 目(2013•R09) ;湖南省高校创新平台开放基金项目(12K070) ;湖南省教育厅一般项目(15C1431) ;中南林业科技大学青年科学研究基金重点项 目(QJ2013005A) ;城市森林生态湖南省重点实验室资助 收稿日期:2016• 03• 01; 网络出版日期:2017• 02• 17 * 通讯作者 Corresponding author.E•mail: csfuywd@ hotmail.com DOI: 10.5846 / stxb201603010354 王震,闫文德,刘曙光,高超,谌小勇.基于 MODIS 数据的中国三种主要土地类型变化的空间特征分析 .生态学报,2017,37(10) :3295• 3301. Wang Z,Yan W D,Liu S G,Gao C,Chen X Y.Spatial•temporal characteristics of three main land•use types in China based on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The overall trend showed that, regardless of the land cover class, the area of improvement was greater than the area of degradation (Table 10), which indicates that the land productivity improved over time. This is consistent with the changes in the characteristics of the three land cover classes in China during the same period as derived by Wang Zhen et al [50]. In recent years, the Chinese government attached great importance to environmental protection.…”
Section: Land Productivity Analysissupporting
confidence: 89%
“…The overall trend showed that, regardless of the land cover class, the area of improvement was greater than the area of degradation (Table 10), which indicates that the land productivity improved over time. This is consistent with the changes in the characteristics of the three land cover classes in China during the same period as derived by Wang Zhen et al [50]. In recent years, the Chinese government attached great importance to environmental protection.…”
Section: Land Productivity Analysissupporting
confidence: 89%
“…where PI is the potential impact index, C is the carbon stock, x is the initial year, y is the end year, La is the land use intensity, A i is the land use intensity classification index for level i, B i denotes the proportion of the area of the land use type in level i, and n is the number of land use levels. In this study, the land use index is divided into four levels, unused land is level 1; forest land, grassland, and water bodies are level 2; cropland is level 3; and built-up land is level 4 [78].…”
Section: Ecosystem Service Vulnerability Assessment Methodologymentioning
confidence: 99%